Drying of salted fish. Comparison between different methods and species - Gísli Kristjánsson 1988- (2013)
Dried salted fish is a popular seafood product in Southern Europe and South America. Large quantities of the salted fish from Iceland are further processed into dried salted products in Portugal before they are sold to the consumer in Portugal or exported to Brazil. By drying the salted fish in Iceland an added value could be achieved in the country before the fish is exported. In this thesis experiments were performed to gather knowledge of drying of salted fish in Icelandic conventional tunnel dryer. Products from different fish species, salting methods and treatments before and during drying are compared. The results showed that there was a great difference in drying rate between ling, tusk and cod. Comparison also showed difference between cod that has been pickle salted, brine salted and injected with Carnal phosphate. Still, no difference in weight loss was observed in drying between brined cod, with and without phosphate, from the same producer. Some advantages can also be achieved by compressing the fish during drying which speeds up water removal and reduces energy cost. All the salted fish had fully saturated brine in the water phase of the muscle and for that reason the fish does not follow normal drying theory. There is no constant drying rate in drying of salted fish, or at least it is very short and therefore the drying curve is different from drying of fresh fish. The humidity and temperature measurements were quite homogeneous through the drying tunnel and no difference could be seen in drying of fish in different locations of the drying tunnel. Results from chemical measurements conducted showed variance in water content and salt content between locations inside the split fish. The surface layer dried fast but inside the fish muscle the water content was still high after drying. Water content measurements using spectroscopic analysis with Near Infrared (NIR) technology showed positive results which have already been shown in an earlier research. Þurrkaður saltfiskur er vinsæl neysluvara í ...